2007
DOI: 10.1152/ajplung.00222.2006
|View full text |Cite
|
Sign up to set email alerts
|

The reverse mode of the Na+/Ca2+ exchanger provides a source of Ca2+ for store refilling following agonist-induced Ca2+ mobilization

Abstract: Hirota S, Pertens E, Janssen LJ. The reverse mode of the Na ϩ /Ca 2ϩ exchanger provides a source of Ca 2ϩ for store refilling following agonist-induced Ca 2ϩ mobilization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
47
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 40 publications
9
47
0
Order By: Relevance
“…Our group reported [35] that the tonic phase of the contraction induced by histamine is partially blocked by KB-R7943 and its effect is not due to the Ca 2+ voltage dependent channel blockage since these had been previously inhibited by Nifedipine. Other groups have reported similar results to ours [116][117][118]. Therefore, it is expected that in the next years different research groups will proceed to investigate if NCX blockers have any kind of therapeutic use in animal Asthma models.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Our group reported [35] that the tonic phase of the contraction induced by histamine is partially blocked by KB-R7943 and its effect is not due to the Ca 2+ voltage dependent channel blockage since these had been previously inhibited by Nifedipine. Other groups have reported similar results to ours [116][117][118]. Therefore, it is expected that in the next years different research groups will proceed to investigate if NCX blockers have any kind of therapeutic use in animal Asthma models.…”
Section: Discussionsupporting
confidence: 83%
“…Hirota et al [98] have also suggested a functional association between the NCX and TRPC activated by store depletion in dog ASM. In that work, several agonists were tested on tracheal rings together with NCX inhibitor KB-R7943 and sensitivity to this drug was observed.…”
Section: Functional Relationship Between Ncx and Ion Channelsmentioning
confidence: 94%
“…Ca 2+ influx can also be influenced by the contractile agonist indicating either activation of receptor-operated channels or a second messenger-operated channel. In addition, the occurrence of Ca 2+ -dependent nonspecific cation currents can lead to increased intracellular Na + and the reversal of Na + /Ca 2+ exchanger to increase Ca 2+ entry [276]. Clearly, ASM cells are well equipped with multiple Ca 2+ import pathways to ensure store refilling.…”
Section: The Influence Of Ca 2+ On the Mechanics Of Asmmentioning
confidence: 99%
“…Ca 2+ influx via the reverse mode of NCX has been suggested to act synergistically with Ca 2+ influx via L-type Ca 2+ channels to trigger Ca 2+ release from the SR as I Ca, L are small at depolarized membrane potential (Sah et al, 2003). In addition, NCX can positively regulate SR Ca 2+ load via the reverse mode action (Hirota et al, 2007). Interestingly, under pathophysiological conditions such as cardiac failure, NCX also operates in the reverse mode to allow additional Ca 2+ influx for contraction in order to compensate for the reduction in Ca 2+ release from SR (Gaughan et al, 1999).…”
Section: Sodium-calcium Exchanger (Ncx)mentioning
confidence: 99%